Effect of thermal treatment on the stability of Na–Mn–W/SiO2 catalyst for the oxidative coupling of methane. (1st March 2021) - Matras, Dorota; Vamvakeros, Antonios; Jacques, Simon D. M.; Grosjean, Nicolas; Rollins, Benjamin; Poulston, Stephen; Stenning, Gavin B. G.; Godini, Hamid R.; Drnec, Jakub; Cernik, Robert J.; Beale, Andrew M.
Abstract : The effect of different calcination protocols on the performance of a Na–Mn–W/SiO2 catalyst is studied with laboratory and synchrotron X-ray based characterisation techniques. Abstract : In this study, we investigate the effect of thermal treatment/calcination on the stability and activity of a Na–Mn–W/SiO2 catalyst for the oxidative coupling of methane. The catalyst performance and characterisation measurements suggest that the W species are directly involved in the catalyst active site responsible for CH4 conversion. Under operating conditions, the active components, present in the form of a Na–W–O–Mn molten state, are highly mobile and volatile. By varying the parameters of the calcination protocol, it was shown that these molten components can be partially stabilised, resulting in a catalyst with lower activity (due to loss of surface area) but higher stability even for long duration OCM reaction experiments.